Marketing strategy from the masters collections. - Safari eBooks (Upper Saddle River, N.J. : FTPress Delivers, 2011)
"Three full books of proven marketing strategy principles and actionable solutions! Discover how to revitalize any brand, and drive it to unprecedented success ... apply the right metrics to all your marketing investments, get accurate answers, and use them to systematically improve ROI ... tightly link marketing with business performance ... bring powerful marketing strategies to the public sector ... and much more! From world-renowned leaders and experts, including Philip Kotler, Nancy R. Lee, Paul W. Farris, Neil T. Bendle, Phillip E. Pfeifer, David J. Reibstein, Larry Light, and Joan Kiddon."--Resource description page.
Marketing in the public sector / Philip Kotler, Nancy Lee -- Marketing metrics, 2nd ed. / Paul W. Farris ... [et al.] -- Six rules for brand revitalization / Larry Light and Joan Kiddon -- Real-time marketing for business growth / Monique Reece.
Title from resource description page (viewed Feb. 4, 2011).
Includes bibliographical references and indexes.
Keywords: Marketing; Marketing -- Social aspects; Branding (Marketing); Electronic books